ORGANIZING MULTI OPTIONAL OFFENSES - Erdem, Can (Sport- és Egészségtudományi füzetek, 2025)
The majority of the offenses in the NBA and European bas-ketball are: ball screen offense, isolation, off ball screen ac-tions and post up plays. Other option can be read and react offense to make our player’s actions unpredictible for the defense. Instead of reacting with different offensive options to defensive tactical changes, multiple option offense will produce fast decision making regarding the defensive con-cept. Therefore the offense will keep up intensity and fast movements without the ball. A well structured read and react offense with combining more and more offensive actions will create more unpredictible offense against any kind of defense.